Abscisic acid dynamics in roots detected with genetically encoded FRET sensors - Jones, Alexander M.; Danielson, Jonas Å. H.; ManojKumar, Shruti N.; Lanquar, Viviane; Großmann, Guido; Frommer, Wolf B. (eLife, 2014)
Fluorescent sensors for the hormone abscisic acid have been developed using a high-throughput platform, and used to monitor hormone dynamics in plant roots and leaves.
Gesehen am 10.05.2017